Institutional framework for the development of project financing in commercial banks - Abdurazakova Nasiba Sultanovna (THE INNOVATION ECONOMY, 2026)
This article studies the institutional foundations of the development of project financing in commercial banks. Project financing is an important financial mechanism that allows for the effective distribution of risks in the financing of investment projects and the attraction of long-term financial resources. In the course of the research, the theoretical aspects of project financing, the institutional role of commercial banks, and the existing problems in this area were analyzed. The article identifies institutional constraints related to the organizational structure of banks, risk management system, regulatory and legal environment, and human resources. Also, scientific and practical proposals and recommendations aimed at improving project financing in commercial banks have been developed. The results of the study are of practical importance in increasing the investment activity of the banking system and developing project financing mechanisms.